(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In 2003, the Philippines, through the Department of Education (DepEd), participated in the global campaign for Education for All (EFA) in the year 2015. This is translated through the implementation of the Alternative Learning System (ALS) Program of DepEd’s Bureau of Alternative Learning System. The Filipino language has its great role in the teaching and learning process in ALS as it is used as the medium of instruction in the National Capital Region. It is one of the major reasons why the researchers aimed to investigate its effectiveness the ALS Program of the DepEd in the National Capital Region (NCR), Philippines. The researchers used the Learning and Training Evaluation theory of Kirkpatrick to evaluate the effectiveness of the use of Filipino (Mother-tongue) in the ALS program through the four level training evaluation models namely Reaction, Learning, Behavior and Results. The program evaluated 126 learning centers located in NCR that consist of 839 learners and 251 Instructional Managers. The Instructional managers rated the use of Filipino language in teaching the ALS as the Very Effective while Effective for the Learners. It is also evident that there is a significant development in the learning and behavior of the learners. Further, there is a significant impact to the family and the community of the learners who undergone the ALS program.